THE INFLUENCE OF THE “KURGILICIN” COMPLEX ON CLINICAL AND BIOCHEMICAL INDICATORS UNDER EXPERIMENTAL STRESS CONDITIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Stress remains one of the most significant physiological challenges affecting metabolic, endocrine, and neuro-motor functions. This study evaluates the effectiveness of the Kurgilicin complex in mitigating stress-induced alterations in experimental animals. Clinical, biochemical, and behavioral parameters were assessed, with a focus on cortisol levels, emotional reactivity, physical endurance, and neuro-motor activity. Findings demonstrate that Kurgilicin exerts protective and corrective effects by reducing stress markers, enhancing endurance, and stabilizing biochemical indicators.